(untitled) (Physical Education, Health and Social Sciences, 2025)
Acute myeloid leukemia (AML) is an abundant type of white blood cells cancer mostly occurs in in adults culminating in deaths. Numerous treatment regimens are available in spite of that many challenges still persist especially in developing countries because they have limited access to early diagnosis, advanced treatments, and supportive care. The aim of this review is to explore the current challenges in diagnosing and management of AML, and to discuss about recent innovations in treatment and diagnostic approaches along with their feasibility. We reviewed published research articles, and review articles from various databases such as Google scholar, Medline, Pubmed, Web of science. Then we extracted relevant information. Major progress has been made in AML treatment, particularly with the introduction of targeted therapies and lower-intensity regimens. For older or unfit patients in whom intensive therapy does not provide favorable outcomes, a combinatory therapy like venetoclax with hypomethylating agents is effective. New drugs such as FLT3 inhibitors, IDH1/2 inhibitors, CPX-351, and gemtuzumab ozogamicin are now part of personalized treatment strategies based on genetic features of the disease. However, access to these therapies and diagnostic tools is still limited in many regions especially developing countries. In spite of innovative treatment regimens death rate after diagnosis remains high in some countries due to late diagnosis, lack of molecular testing, and insufficient supportive care. Although many new treatment regimens are being investigated to treat AML, many patients in still face major barriers to receive immediate and early diagnosis and supportive care. There is a need to expand and equipped healthcare improve access to new therapies, strategies should be made for patient evaluation and treatment planning.